Lost history : the enduring legacy of Muslim scientists, thinkers, and artists - Morgan, Michael Hamilton (Washington, D.C. : National Geographic, 2008)
Author Morgan reveals how early Muslim advancements in science and culture lay the cornerstones of the European Renaissance, the Enlightenment, and modern Western society. As he chronicles the Golden Ages of Islam, beginning in 570 a.d. with the birth of Muhammad, and resonating today, he introduces scholars like Ibn Al-Haytham, Ibn Sina, Al-Tusi, Al-Khwarizmi, and Omar Khayyam--empirical thinkers who revolutionized the mathematics, astronomy, and medicine of their time and paved the way for Newton, Copernicus, and many others. And he reminds us that inspired leaders from Muhammad to Suleiman the Magnificent championed religious tolerance, encouraged intellectual inquiry, and sponsored brilliant artistic, architectural, and literary works. For anyone seeking to understand the major role played by the early Muslim world in influencing modern society, this book provides new insight not only into Islam's historic achievements but also the ancient resentments that fuel today's bitter conflicts.--From publisher description.
Originally published in 2007.
Includes bibliographical references (p. 293-295) and index.
Keywords: Civilization, Islamic; Civilization, Western -- Islamic influences; Muslim scientists; Muslim artists; Renaissance